The systematic and unsystematic factors that affect the liquidity creation of Islamic banks in Malaysia - Lee, Kok Man; Lim, Wooi Tong; Moh, Sau Tung; Ng, Enyang; Wong, June Phin (2019)
This research aims to study the systematic and unsystematic determinants that influence the liquidity creation of Islamic bank in Malaysia. The explanatory variables are categorized into systematic factors and unsystematic factors. The systematic factors include bank’s size, bank’s capital and non-performing financing; meanwhile the unsystematic factors include inflation rate and unemployment rate. This research utilizes the secondary data collected from the data stream for systematic factors as well as yearly financial reports of Islamic banks in Malaysia during the year 2009 to 2017 for unsystematic factors. According to the result, bank’s size, bank’s capital, inflation rate and unemployment rate have significant impact on liquidity creation of Islamic bank in Malaysia. However, the non-performing financing has no significant impact on liquidity creation of Islamic bank in Malaysia. In addition, all of the variables are positively correlated with the Islamic banks’ liquidity creation. Various parties such as government, policy makers, academician and industry can be beneficial from this research paper in enhancing their welfare in relate of liquidity creation determination. Several implications and recommendations were proposed to the related parties and future researches in the last part of the research paper.